Prevalence of Metabolic Syndrome and Its Relation With Pro-Inflammatory Markers Among Group of Libyans - Awami, Salem M.; Mohamed , Faraj Alhomry (Al-Mukhtar Journal of Sciences, 2018)
Metabolic syndrome (Met S) is known as the clustering of several metabolic abnormalities; it can be diagnosed according to several different criteria such as the International Diabetes Federation (IDF) criteria, which is intended for global application in clinical practice. Hematological tests (total Leukocyte count, differential count, platelet count and ESR) has been considered to be a marker of inflammation, several studies have examined the relationship between hematological tests, and components of metabolic syndrome; the data reveals correlations between it and metabolic syndrome in some cross-sectional studies. The study used participants recruited from Albaida and Almarj cities outpatient clinic. History of hypertension, diabetes, Blood pressure, were taken, height, weight, and waist circumference were measured body mass index (BMI, kg/m²) was calculated. Blood samples were collected for hematological tests and others. The study subject was included and categorized according to IDF criteria. A total of 192 residents aged 16 to 85 years were investigated, 80 (41.7%) participants were Males and 112 (58.3 %) were Females. The mean BMI was 29 (St. Dev±07). Rates of underweight, normal weight, overweight and obesity were 4.7%, 24.5%, 27% and 43.75%, respectively.Prevalence of Metabolic Syndrome in our study according to IDF Criteria is 25.5 % ( males 12.5% and females 13%), central obesity, high plasma glucose, high blood pressure, elevated TG accounted for development of Met S.Inflammatory markers showed no significant difference between Met S and None-MetS groups, which could be explained by high prevalence of overweigh and obesity in none-MetSsyndrome persons in our study group